(untitled) (Jurnal Pilar Nusa Mandiri, 2022)
Entering the rainy season with a high level of rainfall will have an impact on vulnerability to floods that will hit a number of areas in various parts of Indonesia. As is often the case in the Gunungsari Sub-district, West Lombok Regency, heavy rains that come early with high intensity for several days often occur, which causes flood disasters and the absence of an automatic system or tool that can detect flooding in the area so that people around the difficulty of detecting floods that come early and cause many people to lose their homes and property due to the flood disaster. The purpose of this study is to provide information related to signs before a flood disaster using the Raspberry Pi 4 as the main tool and the Hc-SR04 ultrasonic sensor as a tool for measuring the distance of an object, where this system can monitor the water level of the river, then disseminate information. related to the water level periodically via Telegram. The test results of the detection sensor system show that the level of accuracy in reading the water level with an average error of 0.48%, indicates that this IoT system has good accuracy.